(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
In this article, a number of scientific studies are given in the world aimed at using and improving "Smart" power supply system’s when ensuring telecommunication equipment with reliable, uninterrupted and high-quality energy. In this area, including Smart Grid systems, special attention is paid to solving many problems, such as the development of models, algorithms, software and modern measures to improve them, devices and tools for remote monitoring of power supply sources, double-sided information system, control of energy consumption, increase in demand for energy.